2007
DOI: 10.1016/j.ijantimicag.2007.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of chloroquine and its hydroxyl analogue to face bacterial, fungal and viral infections in the 21st century

Abstract: Chloroquine (CQ) and its hydroxyl analogue hydroxychloroquine (HCQ) are weak bases with a half-century long use as antimalarial agents. Apart from this antimalarial activity, CQ and HCQ have gained interest in the field of other infectious diseases. One of the most interesting mechanisms of action is that CQ leads to alkalinisation of acid vesicles that inhibit the growth of several intracellular bacteria and fungi. The proof of concept of this effect was first used to restore intracellular pH allowing antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
347
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(360 citation statements)
references
References 127 publications
(124 reference statements)
4
347
0
9
Order By: Relevance
“…The administration of hydroxychloroquine leads to the alkalinization of intracellular acid vesicles that inhibit the growth of several intracellular organisms, facilitating antibiotic efficacy for Coxiella burnetii and Tropheryma whipplei (14,30). Moreover, in vitro data have suggested that the effects of hydroxychloroquine might be generalized for Borrelia burgdorferi (31) and all intracellular organisms that multiply in acidic environments (32). Although antimalarials are generally inactive against most extracellular bacterial species (33), a direct antibacterial effect has been demonstrated, with an in vitro inhibitory effect on the bacterial DNA polymerase of E. coli and Micrococcus luteus (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of hydroxychloroquine leads to the alkalinization of intracellular acid vesicles that inhibit the growth of several intracellular organisms, facilitating antibiotic efficacy for Coxiella burnetii and Tropheryma whipplei (14,30). Moreover, in vitro data have suggested that the effects of hydroxychloroquine might be generalized for Borrelia burgdorferi (31) and all intracellular organisms that multiply in acidic environments (32). Although antimalarials are generally inactive against most extracellular bacterial species (33), a direct antibacterial effect has been demonstrated, with an in vitro inhibitory effect on the bacterial DNA polymerase of E. coli and Micrococcus luteus (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Concentrations higher than 1 mg/ml significantly inhibited the growth of both strains, which could be attributable to the bacteriostatic effects of HCQ (36). Therefore, the level of HCQ released from our device is significantly lower than the levels that inhibit the growth of lactobacilli but is high enough to elicit a therapeutic effect within the FGT.…”
Section: Figmentioning
confidence: 84%
“…SLE patients taking antimalarials are 16 times less likely to develop a major infection [46,47]. SLE patients who require more potent medications (corticosteroids or cytotoxic drugs) may still benefit from antimalarials, as they reduce infection rate, mortality, and have few side effects [4].…”
Section: Antimalarial Drugsmentioning
confidence: 99%